Analyzing the Effect of Paper's Porosity on Trapping and Colour Value - (:unkn) unknown (ASIAN JOURNAL OF CHEMISTRY, 2011)
The acceptance ratio of the second colour printed over the first colour, which is printed on the materials like paper or paperboard is called as trapping. The inks printed on papers having uncoated porous surface dry physically by themselves being absorbed by the celluloses being in the structure of the paper. Knowledge of the absorption behaviour of liquids into porous media has great importance in many application fields. During the physical drying process, formation of the ink on paper having uncoated porous surface occurs substantially due to ink-paper interaction. In that case uncoated so rough paper surface is because of the drying mechanism. The best example for this is the newspaper press. The inks are printed over each other in micro seconds time difference at the moment of CMYK process print. Drying of these inks completely printed on papers having rough surfaces sometimes takes a few days. During that drying process, ink colour changes can occur because of the behaviour of the paper's unstable porosity structure and the acceptance ratio of the inks printed over each other (trapping). These colour changes cause time, labour and financial losses. Solid tone inks printed over each other have standard trapping ratios. There are a few factors affecting the trapping ratios. However, the most important factor is the porosity of the paper. In the study, it is aimed to determine the effect of the paper's porosity on trapping ratios and colour value. This determination is practically done with the test print. Three types of paper having nonporous covered surface, less porous uncoated surface and fungous surface are chosen. Solid tone test prints are made on these papers over and over with physical drying process print inks and IGT CI test print machine by following actuation instructions and 12647-2 printing standard. L*a*b* and trapping values of cyan and magenta colours printed on successively are measured with Gretag Macbeth spectrofotometer via the test prints. Trapping and colour deviations arising from the porosity of paper are determined comparing to the standards.
Keywords: Trapping; Porous paper; Colour deviation; INK COMPONENTS; COATED PAPER